Hanging Baskets. Window Boxes & Containers - Joyce, David (London BCA, 1993)
Covering the basics of planting, plant care and simple propagation techniques, the author looks in turn at hanging baskets, window boxes and other containers using illustrations and step-by-step instructions. The stress throughout is on using the full range of both plant material and containers.
Include Color Illustrations and Index.
Keywords: Hanging baskets -- Container gardening -- Hanging plants -- Patio gardening